Understanding farmers’ intention and willingness to install renewable energy technology: A solution to reduce the environmental emissions of agriculture - Elahi, Ehsan; Khalid, Zainab; Zhang, Zhixin (Applied energy, 2022)
•The article examines farmers’ intention & willingness to install a PV water pump.•Cost of the PV pump was negatively associated with farmers’ intention to install it.•Fewer farmers showed a positive willingness to pay for green electricity.•Young, more educated, and wealthier farmers were more likely to accept green energy.•Government support, education & awareness may increase an acceptance of the PV pump. Although Pakistan has the potential for solar energy generation, only a small proportion of the population uses solar energy technology in agriculture because of its lower public acceptance. This study aims to understand the social acceptance of Photovoltaic (PV) water pumps in rural Pakistan and the farmers’ willingness to pay extra for green electricity. In 2021, cross-sectional data of 1200 farmers were collected from rural Punjab in Pakistan using a well-structured questionnaire. An extension of the Theory of Planned Behaviour (TPB) was used to evaluate farmers’ intentions to install a PV water pump. The extended TPB model was compared with the model of the original TPB and the Theory of Reasoned Action (TRA). Moreover, a parametric econometric approach was used to estimate the determinants of farmers’ willingness to pay extra for green electricity. A comparison of models confirmed that the extended TPB model was performed better than its alternatives because it was associated with the lower value of Root-Mean Square Error of Approximation and the higher value of Comparative Fit Index. The path analysis results showed that the intention to install a PV water pump was positively associated with the coefficients of attitude towards environmental protection, subjective norms of sustainable behaviour, lack of electricity access, perceived behaviour control, and relative advantages. The cost of the PV water pump was negatively associated with the farmers’ intention to install it. The probability of ‘willingness to pay extra for green electricity’ was increased with education, household income, and lack of access to grid electricity but decreased with age and the cost of green energy technology. The findings highlighted that young, more educated, and wealthier farmers were more likely to accept green energy. The lack of financial resources, availability of fossil fuel alternatives, and lack of understanding of green energy technology were the main reasons for the stated unwillingness to pay extra for green energy. Unlikely in resource-rich countries, where people can afford costly green energy, thus far, the government must support the higher price of green energy technology with subsidies in resource-poor countries. Furthermore, providing awareness programs about using a PV water pump to rural populations may enhance public acceptance of the technology.